2021
DOI: 10.1016/j.fbio.2021.101160
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the chemical composition, antioxidant, α-amylase and α-glucosidase inhibition of Moroccan propolis

Abstract: In the present study, seven propolis samples collected from different areas of Morocco were evaluated for various potential attributes. Physicochemical parameters (moisture, pH, soluble substance, insoluble substance, ash content, conductivity, organic matter, resin, balsams, total carbohydrates, total proteins and mineral content), structural characterization by FTIR, phenolic and flavonoid composition and some biological activities (antioxidant, and α-glucosidase and α-amylase inhibitory activities) were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 64 publications
5
22
0
Order By: Relevance
“…Polyphenol compounds are secondary metabolites produced by plants in response to different biotic and abiotic stress conditions [ 42 ]. These chemical compounds are divided into two groups: hydrophilic antioxidants, such as vitamin C and phenolic acids, and lipophilic antioxidants, such as carotenoids, tocopherols, and flavonoids [ 43 ].…”
Section: Bee Bread Compositionmentioning
confidence: 99%
“…Polyphenol compounds are secondary metabolites produced by plants in response to different biotic and abiotic stress conditions [ 42 ]. These chemical compounds are divided into two groups: hydrophilic antioxidants, such as vitamin C and phenolic acids, and lipophilic antioxidants, such as carotenoids, tocopherols, and flavonoids [ 43 ].…”
Section: Bee Bread Compositionmentioning
confidence: 99%
“…Investigational studies have shown that propolis composition varies according to geographic location, botanic origin, and bee species [3,4]. Over 300 chemical components were identified in propolis, such as phenolic acids, flavonoids, and terpenes; these compounds are the most important contributors to the biological activity of propolis [5], including analgesic and anti-inflammatory effects [6,7] and antimicrobial, antioxidative, immunomodulatory, anti-diabetic and anti-tumor activities [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Even though a lower concentration of this medicine is required for inhibition at 50% α-amylase activity when compared to the umbu fruit extract, it is highlighted that this extract, obtained from residue of umbu fruit depulp, presented good inhibitory activity against α-amylase when compared to literature data. Laaroussi et al [36] reported that different propolis samples from Morocco presented IC 50 values between 0.195 and 0.964 mg/mL, being, therefore, higher than that found in umbu fruit extract. This comparison is interesting, because the phytochemical composition of propolis samples indicated the presence of phenolic acids, flavonoids and stilbenes, which is similar to umbu fruit extract composition.…”
Section: α-Amylase Inhibitionmentioning
confidence: 83%